Fantastic Mr. Fox - Dahl, Roald, (1916-1990); Blake, Quentin (New York : Puffin Books, 2007)
Three farmers, each one meaner than the other, try all-out warfare to get rid of the fox and his family.
Ages 8-12.
Keywords: Foxes -- Juvenile fiction; Farmers -- Juvenile fiction